2018
DOI: 10.1002/cpe.4445
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid interpretable credit card users default prediction model based on RIPPER

Abstract: Summary With the vigorous development of the financial sector, financial risks are showing a tendency toward diversification, particularly regarding the customer credit risk of commercial banks. Therefore, the customer's credit risk is being considered by financial institutions, and a credit evaluating model has emerged as a result. Currently, research has concentrated on enhancing the precision of the model, ignoring the interpretability, which makes it difficult to apply in the industry. Compared to precisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 31 publications
(43 reference statements)
0
12
0
Order By: Relevance
“…It has also been observed that in previous studies machine learning models, i.e., random forest [11], stacking [16], the GBDT model [22], logistic model tree [23], bagging [24], and k-nearest neighbor [26] were not given efficient results on imbalanced data on credit card default prediction data, as shown in Figure 5. In previous research, Random forest [11] was given the accuracy of 58.8%, but while combining the random forest with K-means SMOTE oversampling technique, the result has been significantly improved with the accuracy of 88.2%.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…It has also been observed that in previous studies machine learning models, i.e., random forest [11], stacking [16], the GBDT model [22], logistic model tree [23], bagging [24], and k-nearest neighbor [26] were not given efficient results on imbalanced data on credit card default prediction data, as shown in Figure 5. In previous research, Random forest [11] was given the accuracy of 58.8%, but while combining the random forest with K-means SMOTE oversampling technique, the result has been significantly improved with the accuracy of 88.2%.…”
Section: Discussionmentioning
confidence: 95%
“…Various imbalanced datasets like lending club dataset [13,14], Chinese P2P lending company dataset [15], German credit dataset, Australian credit dataset, and Dataset of We.com [16], Chinese consumer finance company dataset [17] were used in the past. Previous studies [2,11,13,[15][16][17][18][22][23][24][25][26] were not deployed in the models for end-users.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A portion of the papers included in this special issue focus on traditional machine learning. Xu et al present a hybrid interpretable model for fraud detection in user credit transactions. Yan et al optimize a neural network with genetic algorithms for finance early warning in the insurance sector.…”
mentioning
confidence: 99%
“…A portion of the papers included in this special issue focus on traditional machine learning. Xu et al 2 It features online transfer learning by utilizing the extracted knowledge from the current state of the tracking targets for generating tracking decisions. Petri Nets are also used for supervised and unsupervised learning.…”
mentioning
confidence: 99%